2012
DOI: 10.4236/ijg.2012.32046
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemical Variations of Groundwater of the Northern Jabal Hafit in Eastern Part of Abu Dhabi Emirate, United Arab Emirates (UAE)

Abstract: This study is aimed to assess and evaluate the suitability of groundwater of the area located to the south-east of Al-Ain area in the UAE using hydrogeochemcical approach. The chemical analyses of groundwater samples collected from the study area showed that the groundwater salinity is high which resulted from heavy groundwater pumping. High chloride concentrations in groundwater of Mubazarah and Neima might be attributed to the entrapped saline water within the limestone sequence of Jabal Hafit, or it can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 3 publications
2
8
0
Order By: Relevance
“…However, there is one sample in the north which displays a higher concentration. The source of sulfate in the study area is the sedimentary rocks, gypsum (CaSO 4 .2H 2 O) and anhydrite (CaSO 4 ) which is present in the study area and was also reported by Murad et al [22].…”
Section: Major Ionssupporting
confidence: 75%
See 3 more Smart Citations
“…However, there is one sample in the north which displays a higher concentration. The source of sulfate in the study area is the sedimentary rocks, gypsum (CaSO 4 .2H 2 O) and anhydrite (CaSO 4 ) which is present in the study area and was also reported by Murad et al [22].…”
Section: Major Ionssupporting
confidence: 75%
“…However, the bicarbonate concentration in Al Khatim is higher in the north with an average concentration of 104.3 mg/L. The sources of bicarbonate are either the presence of carbon dioxide and/or the dissolution of carbonate rocks [22].…”
Section: Major Ionsmentioning
confidence: 96%
See 2 more Smart Citations
“…Considering the statistics and the wells' exploitation and consumption type, the highest usage of the water sources relates to the agricultural use [11]. Plotting the ground water discharge maps, it was revealed that the highest consumption occur around the central part of the plain; hence the effects of ground water flow as well as the decrease in the amount of the entry water into the plain table in changes of the solvents and salinity amounts were analyzed [12] [13].…”
Section: Methodsmentioning
confidence: 99%